New Technology, Work and Employment in the era of COVID‐19: reflecting on legacies of research. (3rd August 2020) - Hodder, Andy
Abstract : The outbreak of COVID‐19 is having a drastic impact on work and employment. This review piece outlines the relevance of existing research into new technology, work and employment in the era of COVID‐19. It is important to be retrospective and undertake both a historically and theoretically informed position on the impact of new technologies in the current crisis and beyond. Issues of control, surveillance and resistance have been central to work on the impact of technology on work and employment and these themes have been identified as central to the experience of work in the current crisis.